Nutritional Investment for Pregnant Mother Through Utilization of Additional Local Foods Made of Carrots - Evi Indriani Br Karo; Febrina Oktavinola Kaban (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
According to nutritional monitoring nutritional status conducted by the Directorate of Public Health, 2017 showing that the percentage of pregnant women at risk of Chronic Energy Deficiency is 14.8%. One of the factors that can cause this problem is due to the lack of knowledge and skills of the mother to fulfill nutrition during pregnancy. Nutritional deficiencies in pregnant women should be avoided, to meet nutritional needs during pregnancy and prevent the consequences of malnutrition, additional food is needed. The type of supplementary food given to pregnant women can be in the form of local food-based PMT or manufacturer's PMT. In accordance with Minister of Health Regulation No. 51 of 2016 concerning Nutrition Supplementation Product Standards. Rumah Berastagi Village is one of the villages in Berastagi Subdistrict, Karo Regency which consists of 4 neighborhoods, one of them is Ujung Aji neighborhood which is the place of this community services. A total of 15 pregnant women are the target of antenatal care. The majority of the community are farmers that planting vegetables and fruits, and one of the vegetable they plant is carrot. The method of community services are education and training. The results of Community Service activities in June 2019, there was an increase in knowledge and skills of pregnant mother to utilized local based food –carrot- as additional nutrition. The results of the examination of Hemoglobin (Hb) levels are able to detect early complications during pregnancy.